PI3K-mTOR-S6K Signaling Mediates Neuronal Viability via Collapsin Response Mediator Protein-2 Expression - Na, Eun J.; Nam, Hye Yeon; Park, Jiyoung; Chung, Myung Ah; Woo, Hyun Ae; Kim, Hwa-Jung (Frontiers in Molecular Neuroscience, 2017)
Collapsin response mediator protein (CRMP)-2 and the mammalian target of rapamycin complex 1 (mTORC1) signaling pathway are associated with common physiological functions such as neuronal polarity, axonal outgrowth, and synaptic strength, as well as various brain disorders including epilepsy. But, their regulatory and functional links are unclear. Alterations in CRMP-2 expression that lead to its functional changes are implicated in brain disorders such as epilepsy. Here, we investigate whether changes in CRMP-2 expression, possibly regulated by mTOR-related signaling, correlates with neuronal growth and viability. Inhibition of mTOR and/or phosphoinositol-3-kinase (PI3K) led to deceased p-S6K, and p-S6 signals also reduced CRMP-2 expression. These changes corresponded to inhibition of neuronal viability and proliferation in cultured hippocampal HT-22 cells under both basal serum-free and serum- or insulin-induced mTOR pathway-activated conditions. CRMP-2 expression tended to be increased by mTOR activation, indicated by an increase in p-S6/S6 level, in pentylentetrazole-induced epileptic rat hippocampal tissues was also significantly reduced by mTOR inhibition. Knockdown of CRMP-2 by si-RNA reduced the neuronal viability without changes in mTOR signaling, and overexpression of CRMP-2 recovered the glutamate-induced neurotoxicity and decrease of mTOR signaling in HT-22 cells. In conclusion, CRMP-2 protein expression controlled by the PI3K-mTOR-S6K signaling axis exerts its important functional roles in neuronal growth and survival.